Functional Assessment for Acute Stroke Trials: Properties, Analysis, and Application - Taylor-Rowan, Martin; Wilson, Alastair; Dawson, Jesse; Quinn, Terence J. (Frontiers in Neurology, 2018)
A measure of treatment effect is needed to assess the utility of any novel intervention in acute stroke. For a potentially disabling condition such as stroke, this outcome measure should include some measure of functional recovery. There are many functional outcome assessments that can be used after stroke. In this narrative review, we discuss exemplars of assessments that describe impairment, activity, participation and quality of life. We will consider the psychometric properties of assessment scales in the context of stroke trials, focussing on validity, reliability, responsiveness and feasibility. We will consider approaches to the analysis of functional outcome measures, including novel statistical approaches. Finally, we will discuss how advances in audio-visual and information technology could further improve outcome assessment in trials.